Preferensi Konsumen terhadap Agroindustri Pliek Ue Melalui Uji Organoleptik dalam Menentukan Kualitas Pliek Ue di Kabupaten Bireuen - Naya Desparita; Syahirman Hakim (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research aims to identify how consumer preferences for pliek ue agroindustry produce quality pliek ue. This research was conducted in July and ended in September 2024 in Bireuen Regency. The research method used is organoleptic testing on 30 agroindustries by 150 consumers as panelists to see the taste, color, texture, aroma, and aftertaste of pliek ue. The results showed organoleptic testing on pliek ue was carried out using 150 consumers as panelists at 30 pliek ue agroindustries in Bireuen Regency. The parameters measured were color, taste, aroma, texture, and aftertaste of pliek ue. The color parameter of pliek ue has an index value of 78%, the taste is 76%, the aroma is 75%, the texture is 80%, and the aftertaste of pliek ue is 78% while the general index value of organoleptic testing is 77.40% classified as moderate. This indicates that the quality of pliek ue produced by agroindustry in Bireuen Regency is medium. Agroindustry parties can improve the quality of pliek ue produced by improving production procedures during fermentation to produce good quality pliek ue. Good quality pliek ue depends on the production process carried out by the agroindustry when producing pliek ue to produce pliek ue that has a pleasant aroma, attractive color, good taste, preferred texture, and the aftertaste does not leave an unpleasant taste to consumers. The pliek ue agroindustry in Bireuen Regency can collaborate with stakeholders to certify the determination of quality standards for the pliek ue category, which has the best quality and can compete with pliek ue in other districts to support the welfare of the pliek ue agroindustry to be more prosperous and consistently produce good quality pliek ue.